2020
DOI: 10.1088/1742-6596/1521/4/042083
|View full text |Cite
|
Sign up to set email alerts
|

The development of chemistry learning devices based blended learning model to promote students’ critical thinking skills

Abstract: The research aims to produce a valid, practical and effective chemistry learning devices based on a blended learning model to improve student critical thinking skills. The 4D development model was applied in this study. Testing of learning devices and tests of critical thinking skills are carried out on the tenth-grade students at high schools in the city of Mataram, West Nusa Tenggara, Indonesia. The one group pretest-posttest design was applied as a research design. The results showed that the validity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
0
18
0
8
Order By: Relevance
“…Symptoms of the problems referred to include: (1) it is difficult for them to work on high-level questions (C4-C6); (2) many of them find it difficult to connect concepts and problems; (3) some of them had difficulty expressing their opinions during the discussion. Besides that, Basri (2019) and Hadisaputra et al (2020) revealed that some students are passive when working on group assignments, students have not been proactive in raising problems in learning, only a few students are involved in answering the problems raised. As a result, students have not been able to provide solutions to the problems found.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptoms of the problems referred to include: (1) it is difficult for them to work on high-level questions (C4-C6); (2) many of them find it difficult to connect concepts and problems; (3) some of them had difficulty expressing their opinions during the discussion. Besides that, Basri (2019) and Hadisaputra et al (2020) revealed that some students are passive when working on group assignments, students have not been proactive in raising problems in learning, only a few students are involved in answering the problems raised. As a result, students have not been able to provide solutions to the problems found.…”
Section: Introductionmentioning
confidence: 99%
“…Some students are still familiar with using rote and memory learning methods. It causes students to quickly forget the information they have received (Hadisaputra et al, 2020). The students' low critical thinking skills are closely related to the weaknesses of the science learning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyebab lainnya dalam proses pembelajaran di sekolah, seperti minimnya pemanfaatan media pembelajaran dalam kegiatan belajar mengajar, sehingga peserta didik kurang aktif dan kurang tertarik dengan materi yang diajarkan. Sementara itu, sekolah memiliki sarana dan prasarana yang memadai untuk menunjang pembelajaran, antara lain laboratorium komputer, laboratorium IPA dan LCD, tetapi penggunaannya belum maksimal (Hadisaputra , et al, 2019;Hadisaputra, et al, 2020).…”
unclassified
“…Mikroskop yang dimaksud adalah mikroskop digital berbasis blended learning (BL), sehingga diharapkan kecerdasan majemuk mahasiswa dapat meningkat. Blended learning (BL) merupakan pembelajaran yang menggabungkan antara sistem e-learning dengan model pembelajaran konvensional atau tatap muka (face-to-face) [10].…”
Section: Pendahuluanunclassified